Repentance, Atonement, and Aquinas - Schmidt, Taylor Greggory (New blackfriars, 2024)
Repentance is central to the message of Christianity. Yet, repentance has received little analysis in recent scholarship despite being emphasized by the church fathers. In particular, there has been minimal effort to understand the necessity of repentance in light of Christ’s atoning work. With this as the background, I explore fundamental questions such as repentance’s definition, scope, and role in salvation history. Furthermore, I attempt to more precisely outline repentance’s role in Christ’s salvific work. Underpinning the project is my view that repentance should be understood as metanoia or transformation. This transformation of repentance is ordered toward divine metanoia – participation in Christ. In developing repentance, I put forward a synthesis of Thomas Aquinas’s framework of penance and John McLeod Campbell’s account of Christ’s vicarious repentance. Through this synthesis, I attempt to make sense of the relationship between repentance and atonement. I finish by suggesting that it would be appropriate to conclude that Thomas would endorse a vicarious repentance account of the atonement and hint at how it might fit into broader soteriologies.